2006
DOI: 10.1016/j.cardiores.2006.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophin is a possible end-target of ischemic preconditioning against cardiomyocyte oncosis during the early phase of reperfusion

Abstract: These results suggest that enhanced relocalization of dystrophin to the sarcolemma during reperfusion may be a mechanistic link between IPC-mediated improvement of mitochondrial function and its protection against oncosis during the early phase of reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…Interestingly, IPC-induced restoration of sarcolemmal dystrophin after reperfusion was dependent on mitochondrial ATP synthesis. 9 These results support the notion that both the sarcolemmal level of dystrophin and mechanical stress during reperfusion are factors determining sarcolemmal permeability and thus susceptibility to reperfusion injury.…”
Section: Article P 2393supporting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, IPC-induced restoration of sarcolemmal dystrophin after reperfusion was dependent on mitochondrial ATP synthesis. 9 These results support the notion that both the sarcolemmal level of dystrophin and mechanical stress during reperfusion are factors determining sarcolemmal permeability and thus susceptibility to reperfusion injury.…”
Section: Article P 2393supporting
confidence: 82%
“…They found that ischemic preconditioning (IPC) restores sarcolemmal dystrophin and suppresses the increase in sarcolemmal permeability after reperfusion. 8, 9 These effects of IPC were enhanced by using BDM to temporarily arrest the heart beat during the early reperfusion period. Interestingly, IPC-induced restoration of sarcolemmal dystrophin after reperfusion was dependent on mitochondrial ATP synthesis.…”
Section: Article P 2393mentioning
confidence: 99%
“…This concentration of BDM has been shown to abolish contractility without an apparent toxic effect in the same experimental model. 24 The PI3K inhibitor, LY294002 (Calbiochem, San Diego, CA, USA), was added at a concentration of 10 μmo/L into the buffers in the presence or absence of BDM for the first 400 s of reperfusion (equivalent to the duration of IPost).…”
Section: Animal Preparation and Perfusion Techniquementioning
confidence: 99%
“…24 The number of EB-positive and -negative cardiomyocytes was counted for 60 high-power fields (magnification × 600) from the endocardium through the epicardium of the mid-LV free wall, and the percentage of EB-positive cardiomyocytes was calculated.…”
Section: Detection Of Oncotic Cardiomyocytesmentioning
confidence: 99%
See 1 more Smart Citation